Comparison of the Stiffness of 3D-Printed Wire Raceway Slewing Bearing Based on Simplified FEA Model and Experiment - GUNIA, Dominik; SMOLNICKI, Tadeusz; STAŃCO, Mariusz (Engineering Transactions, 2023)
The wire-raceway bearings are a subcategory of slewing bearings. Their popularity has recently increased due to their advantages, including weight that is lower than that of other similar slewing bearings, and the ability of transferring various loads, such as axial load, radial load and tilting moment. Currently, metal rings (steel or aluminum) are the most popular choice for all kinds of slewing bearings; however, with advent of additive manufacturing a new ‘chapter’ opens for the development of wire raceway slewing bearings, where the interface between the rolling elements and the raceway is the same as in other bearings (i.e., contact between steel-steel). At the same time, rings can be made from other lightweight materials, such as composites or plastics, with high-level shape customization due to 3D printing. Stress between wire raceways and rings is much lower. Hence, rings’ lower material properties do not significantly affect bearing capacity. Proper calculation methodology should be created to analyze lightweight wire raceway bearings, as materials can differ significantly from typical materials covered by current theories. The paper presents a prototyped 3D-printed bearing with rings made from polylactic acid (PLA). The bearing stiffness is measured and compared with the simplified finite element analysis (FEA) model using the equivalent bearing model with nonlinear springs and beam elements.